Empowering MSMEs Through Student-Led Digital Retail Strategies for Sustainable Development Goals - Kursih Sulastriningsih; Ignatius Agus Supriyono; Mardiana Mardiana; Ardivan Avandi; Kgomotso Moyo (ADI Publisher, 2026)
Digital transformation in the retail sector is progressing rapidly, yet many micro, small, and medium enterprises (MSMEs) continue to face challenges in utilizing technology effectively. This study presents a student-led community empowerment model aimed at optimizing digital retail strategies while supporting the Sustainable Development Goals (SDGs). The study employed a descriptive qualitative approach complemented by quantitative observation and survey data collected from 100 respondents. Students implemented various digital initiatives, including digital branding, content management, marketplace integration, and digital payment systems in participating MSMEs. The findings indicate significant improvements in market reach, customer interaction, operational efficiency, and customer loyalty. The respondent data further support the positive impact of digital strategy implementation and highlight the role of students as mediators of knowledge transfer between academic theory and business practice. This model demonstrates that student involvement in digital retail initiatives can effectively enhance MSME performance while promoting inclusive economic growth, industrial innovation, and responsible consumption aligned with SDGs. The findings also suggest a scalable framework for sustainable community-based economic empowerment.